2013
DOI: 10.1088/1674-1056/22/12/124701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transpiration on unsteady MHD flow of an upper convected Maxwell (UCM) fluid passing through a stretching surface in the presence of a first order chemical reaction

Abstract: The aim of this article is to present the effects of transpiration on the unsteady two-dimensional boundary layer flow of non-Newtonian fluid passing through a stretching sheet in the presence of a first order constructive/destructive chemical reaction. The upper-convected Maxwell (UCM) model is used here to characterize the non-Newtonian behavior of the fluid. Using similarity solutions, the governing nonlinear partial differential equations are transformed into ordinary ones and are then solved numerically b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Table 2 considers a weak concentration ( = 0.5). Finally, Table 3 presents a comparison for − ′′ (0) with Subahs et al [5], Swati et al [9], Hsiao [19], and Sadeghy et al [29]. Table 4 introduces a tabulated data for − ′′ (0) and the modified skin friction at different settings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 considers a weak concentration ( = 0.5). Finally, Table 3 presents a comparison for − ′′ (0) with Subahs et al [5], Swati et al [9], Hsiao [19], and Sadeghy et al [29]. Table 4 introduces a tabulated data for − ′′ (0) and the modified skin friction at different settings.…”
Section: Resultsmentioning
confidence: 99%
“…Subahs et al [5] Swati et al [9] Hsiao [19] Sadeghy et al [29] Present results Table 4 shows the effect of in combination with micropolar effect ( = 2). It presents an increase in the modified skin friction in comparison with part 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Figs. (10)(11)(12)(13) it is observed that for non-Newtonian fluid f, f' and θ profiles increases and profile decreases with the increase in α. With increase in R, θ profile decreases in suction case and increases in injection case, as shown in figs.…”
Section: Solutionmentioning
confidence: 93%
“…Prasad et al [10] examined variable thermos-physical properties of UCM fluid. Mukhopadhyay et al [11] analyzed UCM fluid flow with chemical reaction. Palani et al [12] examined UCM fluid flow with non-linear chemical reaction.…”
Section: Introductionmentioning
confidence: 99%